Submicroscopic subtelomeric aberrations in Chinese patients with unexplained developmental delay/mental retardation - Wang Liwen; Cai Bin; Yang Yanling; Gao Zhijie; Li Jie; Wang Huifang; Xiao Jing; Wang Jingmin; Ji Taoyun; Wu Ye; Zhou Zhongshu; Tian Lili; et al. (BMC, 2010)
Abstract Background Subtelomeric imbalance is widely accepted as related to developmental delay/mental retardation (DD/MR). Fine mapping of aberrations in gene-enriched subtelomeric regions provides essential clues for localizing critical regions, and provides a strategy for identifying new candidate genes. To date, no large-scale study has been conducted on subtelomeric aberrations in DD/MR patients in mainland China. Methods This study included 451 Chinese children with moderate to severe clinically unexplained DD/MR. The subtelomere-MLPA (multiplex ligation dependent probe amplification) and Affymetrix human SNP array 6.0 were used to determine the subtelomeric copy number variations. The exact size and the breakpoint of each identified aberration were well defined. Results The submicroscopic subtelomeric aberrations were identified in 23 patients, with a detection rate of 5.1%. 16 patients had simple deletions, 2 had simple duplications and 5 with both deletions and duplications. The deletions involved 14 different subtelomeric regions (1p, 2p, 4p, 6p, 7p, 7q, 8p, 9p, 10p, 11q, 14q, 15q, 16p and 22q), and duplications involved 7 subtelomeric regions (3q, 4p, 6q, 7p, 8p, 12p and 22q). Of all the subtelomeric aberrations found in Chinese subjects, the most common was 4p16.3 deletion. The sizes of the deletions varied from 0.6 Mb to 12 Mb, with 5-143 genes inside. Duplicated regions were 0.26 Mb to 11 Mb, with 6-202 genes inside. In this study, four deleted subtelomeric regions and one duplicated region were smaller than any other previously reported, specifically the deletions in 11q25, 8p23.3, 7q36.3, 14q32.33, and the duplication in 22q13. Candidate genes inside each region were proposed. Conclusions Submicroscopic subtelomeric aberrations were detected in 5.1% of Chinese children with clinically unexplained DD/MR. Four deleted subtelomeric regions and one duplicated region found in this study were smaller than any previously reported, which will be helpful for further defining the candidate dosage sensitive gene associated with DD/MR.